2021
DOI: 10.1088/1361-648x/ac1f50
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen flow ratio and thermal annealing on defect evolution of aluminum doped zinc oxide thin films by reactive DC magnetron sputtering

Abstract: Al doped ZnO (AZO) is a promising transparent conducting oxide to replace the expensive Sn doped In2O3 (ITO). Understanding the formation and evolution of defects in AZO is essential for its further improvement. Here, we synthesize transparent conducting AZO thin films by reactive DC magnetron sputtering. The effects of oxygen flow ratio as well as the rapid thermal annealing (RTA) in different conditions on their structural and optoelectrical properties were investigated by a variety of analytical techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Post annealing is often used to improve the optoelectronic properties of TCOs even for thin films deposited with substrate heating [42][43][44][45]. Moreover, additional thermal processes are common for solar cells and other devices such as smart windows [46].…”
Section: Post Annealingmentioning
confidence: 99%
“…Post annealing is often used to improve the optoelectronic properties of TCOs even for thin films deposited with substrate heating [42][43][44][45]. Moreover, additional thermal processes are common for solar cells and other devices such as smart windows [46].…”
Section: Post Annealingmentioning
confidence: 99%
“…[33,34] Very recently it was demonstrated that gallium doped zinc oxide and ITO exhibit the same dependence of the selfbias with pressure as reported for AZO, however, only AZO exhibited the most noticeable correlation of the optoelectronic properties with the erosion track. [35] The optoelectronic and analytical properties of AZO thin films by sputtering have been intensively studied including X-ray photoelectron spectroscopy (XPS), [36][37][38][39] , X-ray diffraction (XRD) [36,[39][40][41][42] and Raman [37,40] for various parameters (pressure [43][44][45] , power [46][47][48] , target to substrate distance [32,49] , substrate material [50] , oxygen gas fraction [51,52] , substrate temperature [39] , plasma excitation mode [18,53,54] , annealing temperature, [55,56] target erosion [16] , Al doping fraction [57] ). However, so far, no conclusive correlation has been reported between the role of negative oxygen ions and the physical and chemical properties of AZO thin films as to be able to obtain resistivities below 10 -3 cm for a deposited area comparable with that of the target.…”
Section: Introductionmentioning
confidence: 99%
“…34 The optoelectronic and analytical properties of AZO thin films by sputtering have been intensively studied by X-ray photoelectron spectroscopy (XPS), 35–38 X-ray diffraction (XRD) 35,38–41 and Raman spectroscopy 36,39 for various parameters ( e.g. , pressure, 42–44 power, 45–47 target to substrate distance, 31,48 substrate material, 49 oxygen gas fraction, 50,51 substrate temperature, 38 plasma excitation mode, 18,52,53 annealing temperature, 54,55 target erosion, 16 and Al doping fraction 56 ). However, so far, no conclusive correlation has been reported between the role of negative oxygen ions and the physical and chemical properties of AZO thin films as to be able to obtain resistivities below 10 −3 Ω cm for a deposited area comparable with that of the target.…”
Section: Introductionmentioning
confidence: 99%
“…[16] AZO electrodes still have the disadvantage of lower conductivity compared to ITO, so various methods are needed, such as thermal annealing and plasma treatment, to improve their performance. [17][18][19][20] However, the polymer substrate used to fabricate transparent and flexible electrodes can be easily deformed by thermal stress, which makes it difficult to use the thermal annealing method. [21] Plasma treatment, which can be used at relatively lower temperatures, is considered to be a good alternative to improve sheet resistance.…”
Section: Introductionmentioning
confidence: 99%